Novel biallelic LSS variants in autosomal recessive hypotrichosis simplex: insights from a multi-omics approach - Xiaxia Liu; Kai Liu; Yuda Wei; Yongzhen Qi; Yangyang Luo; Tingli Chen; Xiaohua Ye; Junxu Lu; Yunjia Li; Liangqian Jiang; Juan Teng; Xingzhu Geng; et al. (Human Genetics, 2026)

Projected climate change impacts on crop yields in China's drylands by statistical models and emulators - Shuangshuang Zi; Yiqing Liu; Yan Li; Shuai Wang; Shan Sang; Huiqing Lin; Chengcheng Hou; Fengyu Fu; Bojie Fu (Agricultural Systems, 2026)

Antibacterial gold nanoclusters: Protamine-coated, enzyme-inhibiting nanoparticles combat drug-resistant bacteria and accelerate wound healing - Chengcheng Lin; Ziwei Chen; Ping Zhang; Peng Chen; Yanyan Cui; Xueling Chang; Jian Yang (Journal of Environmental Sciences, 2026)

Non-covalent interactions between lignin and cellulase: From molecular mechanisms to precision regulation - Chengcheng Ye; Yuchen Han; Yanyi Tao; Lin Lv; Yu Long; Jianfeng Wu; Yongcan Jin; Wenjuan Wu (Bioresource Technology, 2026)

Efficient biosynthesis of limonene from sugarcane molasses using engineered yeast - Shengliang Cai; Xiaoyuan Wang; Jingtao Zhou; Chengcheng Yuan; Xiaoling Lin; Lan Wei; Dongying Chen; Pingxu Chen; Chaoyi Zhu; Shuang Li (Biomass and Bioenergy, 2026)

Multi-stage low-carbon planning of hydrogen-based multi-energy microgrids with multiple hydrogen pathways and hybrid uncertainties - Jing Huang; Bangyan Wang; Lin Xue; Chenjia Gu; Yifei Wang; Chengcheng Shao; Xiuli Wang (Journal of Cleaner Production, 2026)

Poricoic acid A administered during DSS exposure attenuates acute colitis in mice and is accompanied by barrier-associated changes and endpoint fecal microbiota shifts - Mei Wang; Kunkun Zhang; Danli Wang; Mingtao Cao; Rong Yong; Xiangqian Li; Wenyi Chen; Chengcheng Peng; Jiale Chang; Lu Fang; Feiyang Zhou; Yuyue Wan; et al. (Journal of Natural Medicines, 2026)

Engineering of a marine cyclodextrin glucosyltransferase for efficient synthesis of 2-O-α-D-glucopyranosyl-L-ascorbic acid using maltodextrin - Wei Wang; Yang Zheng; Jingjing Sun; Chengcheng Jiang; Cong Lin; Jianhua Hao (Systems Microbiology and Biomanufacturing, 2026)

Targeted external donor dosing in single-stage partial nitritation-anammox: A carbon-efficient control framework sustaining ultrahigh total nitrogen removal - Chengcheng Lin; Yanxiao Wei; Sha Wu; Jiao Jin; Yangkai Liu; Hong Chen; Hanbo Yu; Mohd Fadhil Md Din; Eli Hendrik Sanjaya; Binquan Wang (Process Safety and Environmental Protection, 2026)

Fouling behavior and cleaning strategy during treatment of practical refractory organic wastewater using anaerobic ceramic membrane bioreactor - Ruihui Chen; Lixiu Shi; Xinsen Li; Hongming Yang; Sheng Xiang; Mohd Fadhil MD Din; Eli Hendrik Sanjaya; Lu Peng; Zhengwang Wu; Chengcheng Lin; Hong Chen (Journal of Environmental Chemical Engineering, 2026)

Effect of forest trail vegetation density on health benefits: an empirical study based on mobile measurements - Chengcheng Zeng; Ke Wang; Wei Lin; Qibing Chen (European Journal of Forest Research, 2026)

Isotope variability in summer precipitation under the compound effects of moisture source conversion and local meteorological dynamics in the Yellow River Delta, North China - Junxi Lin; Wen Liu; Tao Zhang; Zhiqiang Zhao; Xuchenyu Liu; Guantao Ding; Qiuyu Qiao; Xiaojie Zhong; Lili Zhang; Juping Huang; Jinying Wei; Chengcheng Xia (Climate Dynamics, 2026)

Highly efficient and safe sterilization of reusable medical devices and implants by slightly acidic electrolyzed water - Yan Zhang; Chengcheng Meng; Wenze Ma; Lin Xie; Yi Zhang; Shiwei Liu; Zeliang Chen (Biofouling, 2026)

Nuclear transport factor IPO4 modifies localization by PCV2 and facilitates viral replication - Cui Lin; Chengcheng Wu; Fanfan Zhang; Na Li; Haiqin Li; Lihan Tao; Jia Tan; Yanbing Zeng; Shaopei Fang; Quanyong Zhou (Veterinary Microbiology, 2025)

Fat body specific ABCG3 accounts for xenobiotic tolerance and is regulated by the homeobox transcription factor Bcd in Spodoptera litura - Lin Liang; Long Jin; Furong Mao; Chengcheng Fan; Haoran Kong; Zixin Zhang; Yiou Pan; Qingli Shang (Pesticide Biochemistry and Physiology, 2025)

Stable isotopes reveal the evaporation effects during a drought–flood abrupt alternation period in a semiarid river basin in Inner Mongolia, Northwest China - Jian Luo; Chengcheng Xia; Guoqing Wang; Ruihong Yu; Ruizhong Gao; Xiaomin Liu; Ping Miao; Qiuyu Qiao; Junxi Lin (Journal of Hydrology, 2025)

Unveiling novel steady-state phosphorus removal equilibrium in partial nitritation/Anammox-hydroxyapatite process: underlying mechanisms and microbial metabolism - Yangkai Liu; Yanxiao Wei; Zhenpeng Cao; Chengcheng Lin; Jing Chen; Jingyi Jiang; Jiao Jin; Shengbo Gu; Mohd Fadhil Md Din; Sanjaya Eli Hendrik; Zhihua Liu; Hong Chen (Bioresource Technology, 2025)

The nonstructural protein 13 of porcine deltacoronavirus exhibits an ATP- independent and nondirectional annealing activity that is inhibited by Mg2+ - Lihan Tao; Chengcheng Wu; Cui Lin; Na Li; Shaopei Fang; Jianzhen Huang (Veterinary Microbiology, 2025)

A critical review of oxygen supply and control strategies in single-stage partial nitritation-anammox system for autotrophic nitrogen removal from wastewater - Sha Wu; Fei Gao; Chengcheng Lin; Yijie Quan; Yanxiao Wei; Zhihua Liu; Hanbo Yu; Eli Hendrik Sanjaya; Mohd Fadhil Md Din; Hong Chen (Journal of Environmental Chemical Engineering, 2025)

An improved sample preparation method for strontium isotope stratigraphy: case study of early Miocene oysters and foraminifera from the Gulf of Suez, Egypt - Ting Ruan; Yue Cai; Qimei Guo; Nicholas Christie-Blick; Ahmed N. El-Barkooky; Abdel-Moneim El-Araby; Ahmed Zakaria; Zhengfan Lin; Chengcheng Wang; Raed Badr (Applied Geochemistry, 2025)

Multiple behaviour recognition of free-range broilers in cross-domain scenarios using MCA-YOLOv5 - Yang Guo; Junshu Wang; Peng Lin; Chengcheng Yin; Yuxing Han (Biosystems Engineering, 2025)

Occurrence and ecological risks of pharmaceuticals along the Yangtze River Basin of China: Insights from target analysis and suspect screening strategy - Chong Chen; Chengcheng Bu; Qi Wang; Yutong Zhang; Shaopeng Xu; Yu Hua; Ruolan Jia; Huiju Lin; Xiaolei Wang; Zhiwei Gan; Xiong Xiong; Limin Ma; et al. (Journal of Hazardous Materials, 2025)

Triple-gradient porous fibrous membranes with decoupled energy-mass transfer for sustainable solar desalination - Yecheng Wang; Chengcheng Li; Peng Zhu; Zubin Wu; Shishi Lin; Xuehong Jiang; Yang Cao; Shen Li; Wei Huang (Chemical Engineering Journal, 2025)

Delineate the unknown aquifer geometry and boundary condition using hydraulic tomography - Mpendulo Mangaliso Mtsetfwa; Zaiyong Zhang; Chengcheng Gong; Hong-Ru Lin; Jet-Chau Wen; Yu-Li Wang (Journal of Hydrology, 2025)

Differential analysis and unified predictive modeling of capillary rise in sodium chloride and sodium sulfate saline soils - Yupeng Shen; Lin Wang; Quan Cao; Jamlick Kariuki; Chengcheng Luo (Arabian Journal of Geosciences, 2025)

Novel one-step method to construct gellan gum-zein core-shell structured starch beads for regulating starch digestion - Zhiwei Lin; Weixian Li; Chengcheng Zhang; Linjie Zhan; Xiaoyang He; Yang Qin; Qingjie Sun; Na Ji (Food Chemistry, 2025)

Clinical efficacy and safety of vortioxetine as an adjuvant drug for patients with bipolar depression - Chunxiao Dai; Yaoyang Fu; Xuanwei Li; Meihua Lin; Yinbo Li; Xiao Li; Keke Huang; Chengcheng Zhou; Jian Xie; Qingwei Zhao; Shaohua Hu (Journal of Zhejiang University-SCIENCE B, 2025)

Unraveling the role of freight facility development in the dynamics of gentrification - Zhengtao Qin; Chengcheng Yu; Haocheng Lin; Chao Yang; Quan Yuan (Transportation Research Part D: Transport and Environment, 2024)

The combination of HSI and NMR techniques with deep learning for identification of geographical origin and GI markers of Lycium barbarum L. - Chengcheng He; Xin Shi; Haifeng Lin; Quanquan Li; Feng Xia; Guiping Shen; Jianghua Feng (Food Chemistry, 2024)

Multi-omics integration analysis: Tools and applications in environmental toxicology - Chengcheng Shi; Lin Cheng; Ying Yu; Shuangshuang Chen; Yubing Dai; Jiajia Yang; Haijun Zhang; Jiping Chen; Ningbo Geng (Environmental Pollution, 2024)

Improved activity and significant O2 resistance of Cs doped Co3O4 catalyst for N2O decomposition - Hongyu Zhao; Pan Wang; Zonglin Li; Chengcheng Ao; Xuteng Zhao; He Lin (Journal of Environmental Chemical Engineering, 2024)

High-performance solar water purification enabled by controlled water convection in integrated porous aerogel multistage distiller - Chengcheng Li; Zhen Li; Peng Zhu; Weihua Mao; Yecheng Wang; Shishi Lin; Yang Cao; Jun Liu; Mingxin Zhang; Shuyi Huang; Wei Huang (Chemical Engineering Journal, 2024)

Creating most needed customized bus services: A collaborative analysis of user-route dynamics - Chengcheng Yu; Haocheng Lin; Yitong Chen; Chao Yang; Ailing Yin; Quan Yuan (Transportation Research Part D: Transport and Environment, 2024)

Preparation of ionic porous polymers for extraction of four phenolic endocrine disrupting chemicals from fish and water samples - Chengcheng Fan; Chenhuan Wang; Bin Zhao; Zixuan Cai; Qianqian Wang; Lin Hao; Zhi Wang; Qiuhua Wu; Chun Wang (Food Chemistry, 2024)

Integrated strategies for road transportation-related multi-pollutant control: A cross-departmental policy mix - Chengcheng Yu; Zhengtao Qin; Yougeng Lu; Haocheng Lin; Chao Yang; Quan Yuan; Qingyang Wu (Transportation Research Part D: Transport and Environment, 2024)

Thermal−hydraulic characteristics of R32 and R410A condensation in plate heat exchangers with 1 mm chevron depth - Wenjian Wei; Kaibing Lin; Yubin Du; Chengcheng Xu; Xiaolu Li (International Journal of Refrigeration, 2024)

Natural or balanced? The physiological and psychological benefits of window views with different proportions of sky, green space, and buildings - Tianyi Yao; Wei Lin; Zhiyi Bao; Chengcheng Zeng (Sustainable Cities and Society, 2024)

Tumor microenvironment responsive multifunctional smart living materials based on engineered bacteria for inducing macrophage polarization to enhance tumor immunotherapy - Ning Jiang; Kui Zhao; Chengcheng Liu; Xiaojuan Zhu; Xumeng Huang; Lin Yang; Xiaoping Yi; Yingping Zhuang; Bangce Ye; Jiangchao Qian; Jiaofang Huang (Chemical Engineering Journal, 2024)

Mercury pollution risks of agricultural soils and crops in mercury mining areas in Guizhou Province, China: effects of large mercury slag piles - Chengcheng Zhang; Tianxiang Xia; Lina Zhang; Zhuo Chen; Haonan Zhang; Xiaoyang Jia; Lin Jia; Xiaoying Zhu; Guangbing Li (Environmental Geochemistry and Health, 2024)

Hyporheic exchange and nitrogen cycle processes under the dual effects of flooding and heterogeneous streambed - Yuzhu Lin; Chengpeng Lu; Chengcheng Wu; Bo Liu; Longcang Shu (Journal of Hydrology, 2023)

The therapeutic look up: Stress reduction and attention restoration vary according to the sky-leaf-trunk (SLT) ratio in canopy landscapes - Wei Lin; Chengcheng Zeng; Zhiyi Bao; Hexian Jin (Landscape and Urban Planning, 2023)

Zirconium tungstate reinforced energetic composites with inhibited thermal expansion and reduced thermal stress - Congmei Lin; Liangfei Bai; Liyuan Wei; Ruqin Liu; Shiliang Huang; Cui Zhang; Xiaoqing Tu; Zhijian Yang; Feiyan Gong; Chengcheng Zeng; Ling Ding; Liping Pan; et al. (Chemical Engineering Journal, 2023)

Accelerated removal of five pesticide residues in three vegetables with ozone microbubbles - Xiaohan Li; Chengcheng Liu; Fengmao Liu; Xianzhao Zhang; Qingrong Peng; Ge Wu; Jin Lin; Zhanping Zhao (Food Chemistry, 2023)

Bistable electrochromic dual-output array display based on intramolecular proton coupled electron transfer - Chengcheng Wang; Jiashuang Li; Wenhua Lin; Jingwen Wang; Yuhua Chen; Bingzhen Li; Liping Zhang; Shaohai Fu (Chemical Engineering Journal, 2023)

Rock burst initiation and precursors in a model specimen based on acoustic emission and infrared monitoring - Manqing Lin; Chengcheng Gao; Yuanyou Xia; Dianji Zhang; Xiqi Liu; Xiaoshuai Liang (Arabian Journal of Geosciences, 2022)

Megafaunal Community Structure From the Abyssal to Hadal Zone in the Yap Trench - Dongsheng Zhang; Yadong Zhou; Jichao Yang; Thomas Linley; Ruiyan Zhang; Bo Lu; Peng Xu; Chengcheng Shen; Shiquan Lin; Yueyun Wang; Dong Sun; Xiaogu Wang; et al. (Frontiers in Marine Science, 2021)
Hadal trenches remain one of the unexplored ocean ecosystems due to the challenges of sampling at great depths. It is still unclear how a faunal community changes from the abyssal to the hadal zone, and which environmental variables are the key impacting factors. In this study, nine dives of the Human Occupied Vehicle (HOV) “ JIAOLONG ” were conducted from abyssal to hadal depths (4,435–6,796 m) in the Yap Trench on the southeastern boundary of the Philippine Sea Plate in the western Pacific, divided into 48,200 m video transects, to describe the megafaunal communities and reveal their relationship with environmental factors. A total of 1,171 megafauna organisms was recorded, 80 morphospecies (msps) from 8 phyla were identified based on the video data, most of which were reported for the first time in the Yap Trench. Arthropoda was the most abundant phylum and Echinodermata was the most diverse phylum of the megafaunal community. The faunal abundance increased with depth, whereas the Shannon diversity index decreased with depth. Cluster analysis suggested seven assemblages, with five abyssal groups, one mixed group, and one hadal dominant group. Although megafaunal communities changed gradually from abyssal zone to hadal zone, both PERMANOVA and PERMDISP analyses revealed that the communities are significantly different between abyssal zone and hadal zone, indicating 6,000 m as the boundary between the two depth zones. Depth, substrate, slope, and latitude were identified as four important environmental factors with significant influence on megafaunal community structure. This study proposed a transition pattern from the abyssal to hadal zone in the Yap Trench, highlighted the importance of habitat heterogeneity in structuring megafaunal community in a hadal trench.

Coexpression network revealing the plasticity and robustness of population transcriptome during the initial stage of domesticating energy crop Miscanthus lutarioriparius - Shilai Xing; Chengcheng Tao; Zhihong Song; Wei Liu; Juan Yan; Lifang Kang; Cong Lin; Tao Sang (Plant Molecular Biology, 2018)